Competency Assessment of Project Managers of a National NGO in India. (September 2021) - Sandhu, Monisha Vaid; Liang, Zhanming
Public health projects carried out by non-government organisations (NGOs) are considered a critical contributor in the provision of health services to rural population in India. But there is clear lack of documented evidence that describes the capacity and competency of the NGO project managers to successfully design and implement a new project. This article presents findings of an exploratory case study using outreach model of family planning service delivery as an example to understand the steps and actions taken by senior managers throughout the project's life cycle and competencies required by them to execute the project. Focus group discussion followed by paper-based survey using sections of Management Competency Assessment Tool was conducted with senior managers of the chosen NGO. The results indicate that the strategies developed by the NGO managers are consistent with the existing literature on project management. However, not all managers have the same level of confidence in demonstrating the competencies of (a) knowledge of healthcare environment; (b) evidence informed decision making; and (c) interpersonal, communication qualities and relationship management. The organisation needs to invest in human resource development using mixed approach of providing training, team building activities, mentoring, and support.